Impact of government incentive on MSME innovation - Francis Mark A. Quimba; Maureen Ane D. Rosellon (Philippine Institute for Development Studies (PIDS), 2019)
MSMEs find it challenging to undertake innovation activities given their limited resources and capabilities. Studies on innovation in MSMEs have identified internal and external factors that affect innovation capabilities and activities, one of which is government support. Incentives such as tax deductions/credits, grants, subsidies and other similar instruments have been used by governments to promote innovation especially in MSMEs. Using the 2015 Survey of Innovation Activities of Establishments, this paper presents a profiling of innovation activities and characteristics of surveyed MSMEs in the Philippines, and attempts to estimate the impact of government incentives on their innovation behavior and outcomes. Findings indicate that more MSMEs undertake knowledge management, organizational and marketing innovationthan product or process innovation. Receipt of government financial support for innovation activities was found to have a positive impact on organizational and marketing innovation.
Keywords: 330; MSMEs; SMEs; innovation; government incentives; government support; innovation factors